The Updated Sydney System: Classification and Grading of Gastritis as the Basis of Diagnosis and Treatment. (1st September 2001) - Stolte, Manfred; Meining, Alexander
Abstract : In recent years, the importance of the histological diagnosis of gastritis on the basis of routinely obtained antral and corpus biopsies has increased enormously, which is owed not least of all to the discovery of Helicobacter pylori . The introduction of the Sydney system made it possible, for the first time, to grade histological parameters, identify topographical distribution and, finally, make a statement about the etiopathogenesis of the gastritis. Of pathogenetic importance is, in the first instance, the differentiation between gastritis with and gastritis without H pylori infection. The group of H pylori -associated gastritis can be further subdivided into forms of gastritis whose morphological distribution patterns usually identify them as sequelae of H pylori infection, while the group of gastritis unassociated with H pylori, can be differentiated into autoimmune, chemically induced reactive gastritis, ex- H pylori gastritis, Helicobacter heilmannii gastritis, Crohn's gastritis and a number of special forms of gastritis.